2006
DOI: 10.1385/bter:109:1:035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Fluoride and Caffeine on the Kidney Function and Free-Radical Processes in that Organ in Adult Rats

Abstract: An experiment was carried out on Sprague-Dawley rats (adult males) that for 50 days were administered, in the drinking water, NaF and NaF with caffeine (doses, respectively: 4.9 mg of NaF/kg body mass/24 h and 3 mg of caffeine/kg body mass/24 h). Disturbances were noted in the functioning of kidneys, which were particularly noticeable after the administration of NaF with caffeine. Changes in the functioning of kidneys were also confirmed by such parameters as the level of creatinine, urea, protein, and calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The observed increased serum creatinine in the caffeine and kolanut treated groups indicates that chronic consumption of caffeine or kolanut may result in renal dysfunctions and development of nephritis (Ikegwuonu et al, 2006). The significant decrease in serum lipid profile in the this study is in agreement with previous study which showed that triglycerol level was decreased after treatment with caffeine (Ikegwuonu et al, 1981;Birkner et al, 2006). Also, the observed significant increase in glycerol, total cholesterol, HDL, LDL, VLDL and triglycerides in caffeine groups and decaffeinated kolanut extracts treated animals in this study agree with other reports (Curb et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed increased serum creatinine in the caffeine and kolanut treated groups indicates that chronic consumption of caffeine or kolanut may result in renal dysfunctions and development of nephritis (Ikegwuonu et al, 2006). The significant decrease in serum lipid profile in the this study is in agreement with previous study which showed that triglycerol level was decreased after treatment with caffeine (Ikegwuonu et al, 1981;Birkner et al, 2006). Also, the observed significant increase in glycerol, total cholesterol, HDL, LDL, VLDL and triglycerides in caffeine groups and decaffeinated kolanut extracts treated animals in this study agree with other reports (Curb et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Transaminases play an important role in protein and amino acid metabolism which are found in the cells of almost all the body tissues and when diseases or injuries affected these tissues, they are released into the blood stream (Kuzminskaya and Bersan, 1975). Increase in serum ALP may be considered as an indicator of cholestasis, which may result from intracellular hepatic canaliculli obstruction associated with inflammation (Birkner et al, 2006). Since we did not study the histology of the internal organ in this present study, it will not be unreasonable to conclude that cholestasis is responsible for the observed significant increases in the level of both ALT and ALP in the caffeine treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) activity was however significantly raised in the plasma and this increase may be considered as an indicator of cholestasis that may result from intracellular hepatic canaliculi obstruction associated with inflammation (Birkner et al, 2006). However, plasma ALP activity like AST may also be affected by sources in the body other than the liver, limiting its use as a marker of hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The raised concentration of protein after caffeine administration to rats was also observed by Grucka-Mamczar et al (11,12). Birkner et al (2,3) consider that an increased level of protein after administration of caffeine is caused by intensified renal filtration and diuresis. In such circumstances, there is increased urea and creatinine excretion by the kidneys.…”
Section: Discussionmentioning
confidence: 99%